What is oyster shell recycling? - Ana Zangroniz; Marian Azeem-Angel; Katie Heiden; Heather Donnelly; Ashley Smyth (EDIS)
This new 7-page publication of the UF/IFAS Department of Soil and Water Sciences is intended to serve Natural Resources or Florida Sea Grant Extension agents, as well as local partners considering establishing a local oyster shell recycling program or local restaurants interested in learning more about oyster shell recycling, and shares lessons learned from starting a program in Miami-Dade County. Written by Ana Zangroniz, Marian Azeem-Angel, Katie Heiden, Heather Donnelly, and Ashley R. Smyth.